Estimation of probable maximum precipitation for one day duration: A case study of Gujjar Khan in Potwar region, Pakistan - Boota, Muhammad Waseem; Nabi, Ghulam; Ahsan, Haseeb; Abbas, Tanveer (Journal of Himalayan Earth Sciences, 2015)
Daily rainfall data of Gujjar khan for a period of 30 years (1961-1990) were collected from Pakistan meteorological department (PMD), Lahore. Annual maximum one day precipitation was sorted from the precipitation data to compute the probable maximum precipitation (PMP) for 1-day duration. The Hershfield technique and Gumble distribution of extreme values were used for the estimation of 1-day probable maximum precipitation based on frequency factor. The frequency factor was used to compute for 1-day PMP values in the study area. The PMP for Gujjar khan was estimated to be 357.39 mm and the ratio of the 1-day PMP to highest 1-day precipitation was 1.19. The maximum 1-day precipitation for different return periods 2, 5 10, 20, 25, 50, 100, 200, 500 and 1000 years were also estimated. The estimated maximum rainfall and PMP values could be useful in designing of soil and water conservation practices, design of small dams in the study area.